Corporate Carbon and Financial Performance Revisited. (March 2022) - Busch, Timo; Bassen, Alexander; Lewandowski, Stefan; Sump, Franziska
To assess the robustness and sensitivity of the findings in Delmas, Nairn-Brich, and Lim, we conduct a replication and an extension study. In the replication, we use their research design but analyze another time frame. In our extension, we furthermore expand the geographical scope, and use another carbon performance measure as well as a different set of control variables. We show that the finding that higher carbon emissions are associated with higher short-term financial performance is very robust. By contrast, we also find strong evidence for higher carbon emissions being associated with higher long-term financial performance. This outcome is supported by several supplementary analyses and robustness checks. We derive theoretical implications for the debate on tackling grand challenges. Since there seem to be negative financial performance implications for firms reducing carbon emissions, we highlight a clear need for further policy intervention to pave the way for a low-carbon economy.